MINI-INVASIVE (PUNCTURE-DRAINING) ECHO-CONTROLLED INTERVENTIONS IN THE PATHOLOGY OF THE ABDOMINAL CAVITY - A.I. Kolosovych; R.A. Sydorenko; A.M. Tsyganok (Bogomolets National Medical University, 2018)
Puncture-draining interventions under the ultrasound control have become an indispensable effective aid in complex treatment, and in some cases, an independent method of correcting a number of diseases of the abdominal cavity. However, some technological aspects in the execution of the procedure and the postoperative management of patients are left out of the focus of discussion. The aim - to improve the results of the use of puncture drainages under ultrasound control in abdominal pathology. Puncture-draining interventions are applied in 89 patients: with pancreatogenic fluid collections, intra-abdominal complications after abdominal operations, inflammatory processes in the gallbladder, tumor bile duct obstructions, liver abscesses. An analysis of the effectiveness of the use of puncture and drainage interventions under ultrasound control in pathology of the abdominal cavity organs and retroperitoneal space was carried out. Puncture-draining interventions under ultrasound control are an alternative to open surgical interventions, especially in patients with severe concomitant pathology, severe general condition. In this case, they can be as element (stage) of complex treatment and an independent, final method of surgical care. The choice of echo-controlled interventional technologies as a method of operational correction should be carried out with understanding their capabilities. The effectiveness of such mini-invasive methods allows us to recommend their acceptance in surgical hospitals for diseases of the abdominal cavity organs and retroperitoneal space.